Mass sports of students and cadets which server military contract in positions of officers - Anastasia Bondar; Svitlana Kondraschenko (Kharkiv State Academy of Physical Culture, 2015)
Purpose: study of features of organization of mass sports of students and cadets which server military contract in positions of officers. Material and Methods: analysis of literary sources and documents, analysis of the systems, questioning (questionnaire), methods of the mathematical processing of data. In a questionnaire 97 respondents - 29 cadets of a 5 course and 68 students of 4 courses of military-legal faculty of the Yaroslav Mudryi National law university. Results: 69% cadets and only 35% students are engaged in the different types of motive activity in free time, here 48% cadets and 43% students elect the playing types of sport (football, volley-ball, basket-ball), 65,5% cadets and 48,5% students go in for sports for self-perfection and self-realization, here 45% cadets and 32% students plan necessarily to prolong to be engaged in the select type of sport upon termination of studies in higher educational establishment. Conclusions: the Study 4th Year Students And Students Of The 5th Year Of Military Faculty Of Law Has Shown That The Students Serious About Their Chosen Profession And Understand The Importance Of Physical Fitness In A Future Service, They Are Able To Objectively Assess The Level Of Their Physical Readiness And Are Ready For Further Self-Improvement